The feminized outcast: Gendering male marginality in Panait Istrati’s Kyra Kyralina - Mitrulescu, Corina Mariana (Swedish Journal of Romanian Studies, 2026)
This paper examines the construction of masculinity in Panait Istrati’s Kyra Kyralina (1926/1971) through a gender-critical lens, focusing on the largely neglected queer figure of Stavro. While existing scholarship has predominantly addressed the novel’s exoticism and autobiographical elements, or the transgressive femininity of Kyra, comparatively little attention has been paid to the gendered complexity of its male protagonist. By foregrounding Stavro’s life narrative, this paper seeks to reassess Kyra Kyralina as a significant early twentieth-century exploitation of subordinated and queer masculinity. Drawing on Judith Butler’s theory of gender performativity (1990/2006) and R.W. Connell’s model of hierarchical masculinities (1992/2005), the article conceptualizes masculinity as socially constructed, performative, and coercively regulated rather than a stable identity. Butler’s framework enables an analysis of Stavro’s repeated failure to embody hegemonic masculine norms such as authority, autonomy, and heterosexual dominance, while Connell’s typology elucidates the structural mechanisms through which such failures result in subordination, stigmatization, and vulnerability to violence. Together, these perspectives illuminate how masculinity is constituted in Istrati’s text through marginalization. The paper offers close readings of key episodes from the novel, including Stavro’s exposure to sexual exploitation, his homoerotic desire, and his social marginalization. These experiences are analyzed not as incidental biographical details, but as formative processes through which Stavro’s gendered identity is produced. Rather than presenting suffering as character-building or redemptive, Istrati depicts trauma as central to the formation of masculinity, challenging dominant literary tropes that equate male hardship with moral or heroic development. Most importantly, the paper argues that Istrati does not moralize or sensationalize queer desire. Instead, homosexuality is portrayed as intertwined with longing, confusion, and affective attachment, while social condemnation and coercion are shown to originate from surrounding patriarchal order. In this respect, the novel anticipates later queer trauma-informed approaches to gender by exposing the human cost of rigid normative frameworks. By repositioning Stavro at the center of gender analysis, this study contributes to a growing body of scholarship that reconsiders early twentieth-century literature as the site of critical engagement with masculinity. It ultimately argues that the text offers a prescient critique of gender norms, revealing masculinity as hierarchical and unstable, an insight that remains highly relevant to contemporary gender studies.